Accurate compact flowfield-dependent variation method for compressible euler equations - Abdulhafid, M. Elfaghi; Waqar, Asrar; Ashraf, A. Omar (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.